PENGELOMPOKAN KABUPATEN/KOTA DI JAWA TIMUR BERDASARKAN KASUS STUNTING BALITA MENGGUNAKAN ALGORITME FUZZY PARTICLE SWARM OPTIMIZATION-FUZZY C-MEANS - Sepnita Wulandari; Robert Kurniawan (Jurnal Statistika Universitas Muhammadiyah Semarang, 2019)
Stunting is a condition that describe the presence of chronical malnutrition problem caused by various condition. East Java Province is a region that has the highest percentage of short toddler in Java Island. Moreover, there is high disparity in cross regency/city and the prevalence rate of stunting in the East Java Province is same as national prevalence rate. Meanwhile, Rencana Pembangunan Jangka Menengah Nasional (RPJMN) 2015-2019 sets the target of national prevalence rate of stunting toddler decreasing in 2019. Based on that problem, this research is clustering regency/city in East Java Province based on stunting toddler case. The clustering uses Fuzzy Particle Swarm Optimization-Fuzzy C-Means (FPSO-FCM). From the clustering result, this research obtains 2 cluster which are cluster of low stunting potential region (cluster 1) and high stunting potential region (cluster 2).